ANALYSIS OF THE FINANCIAL PERFORMANCE OF TEKULAI BUGIS VILLAGE USING THE RATIO OF INDEPENDENCE, GROWTH AND EFFECTIVENESS - Yulia Citra; Raju Maulana; Muhammad Fauzan (Indragiri Research Center (ingreat), 2026)
This study aims to analyze the financial performance of Tekulai Bugis Village, Tanah Merah District, Indragiri Hilir Regency based on the independence ratio, effectiveness ratio, and growth ratio. The research method used is quantitative descriptive with an approach to analyze financial ratios to the realization data of the Village Revenue and Expenditure Budget (APBDes) for 2024–2025. Data was obtained through documentation of village financial statements which were then analyzed using the calculation of the ratio of independence, effectiveness, and growth. The results show that the ratio of village financial independence is in the very low category, which is 0.02% in 2024 and increases to 0.03% in 2025, which indicates the high dependence of villages on transfer funds from the central and regional governments. The effectiveness ratio shows effective performance with an achievement of 100% in 2024 and 2025, which means that the realization of Village Original Income (PADes) has been in accordance with the set target. Meanwhile, the PADes growth ratio shows a positive trend, namely 170.07% in 2024 and 21.62% in 2025, although nominally it is still relatively small. In conclusion, the financial performance of Tekulai Bugis Village shows good effectiveness in achieving revenue targets, but the level of financial independence is still very low so that the village is still dependent on transfer funds. It is necessary to optimize the potential of Village Original Income (PADes) to increase village fiscal independence.